Implementasi Text Clustering Terkait Pilpres 2024 Menggunakan Metode K-Means - Miquel Yosafat; Jatmika (Universitas Kristen Immanuel, 2024)
This research focuses on implementing the K-Means Clustering method to analyze public opinion regarding the 2024 presidential election. The K-Means algorithm, as a data mining method without direction, is used to group opinion data that has similar characteristics. The results of the cluster analysis confirmed the absence of text that was sarcastic or sarcastic in the Twitter data taken. Clusters were divided and categorized based on the text approach, and the results showed that the word